2012
DOI: 10.1002/jcp.22974
|View full text |Cite
|
Sign up to set email alerts
|

3,5,3′triiodo‐L‐thyronine induces SREBP‐1 expression by non‐genomic actions in human HEP G2 cells

Abstract: Liver is an important target for thyroid hormone actions. T(3) exerts its effects by two mechanisms: (i) Genomic actions consisting of T(3) link to nuclear receptors that bind responsive elements in the promoter of target genes, (ii) non-genomic actions including integrin αvb3 receptor-mediated MAPK/ERK and PI3K/Akt/mTOR-C1 activation. SREBP-1a, SREBP-1c, and SREBP-2 are transcription factors involved in the regulation of lipogenic genes. We show in Hep G2 cells that T(3) determined a dose- and time-dependent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 63 publications
1
40
0
Order By: Relevance
“…Although there have been no reports on the promoter regions of VSIG4, in silico data and nucleotide sequence analysis of the upstream elements of the transcription start site of VSIG4 have identified regulatory trans-acting factor binding sites for factors such as glucocorticoid receptor, c-myb, and SREBP-1 (Genecard database). The expression of SREBP-1 has recently been reported to be negatively regulated by classical PKC isoforms such as PKCa in Hep G2 cells in response to 3,5,39-triiodothyronine (35). It would be of interest to determine, in future studies, whether PKCa negatively regulates CRIg expression by downregulating SREBP-1 expression, resulting in reduced CRIg transcription.…”
Section: Discussionmentioning
confidence: 99%
“…Although there have been no reports on the promoter regions of VSIG4, in silico data and nucleotide sequence analysis of the upstream elements of the transcription start site of VSIG4 have identified regulatory trans-acting factor binding sites for factors such as glucocorticoid receptor, c-myb, and SREBP-1 (Genecard database). The expression of SREBP-1 has recently been reported to be negatively regulated by classical PKC isoforms such as PKCa in Hep G2 cells in response to 3,5,39-triiodothyronine (35). It would be of interest to determine, in future studies, whether PKCa negatively regulates CRIg expression by downregulating SREBP-1 expression, resulting in reduced CRIg transcription.…”
Section: Discussionmentioning
confidence: 99%
“…A second clue indicating that T 2 has contrasting effects on hepatic lipogenesis involving SREBP-1c was found in vitro. T 3 increases an active precursor of SREBP-1c in HepG2 cells without modulating SREBP-1c transcription (Gnoni et al 2012). T 2 , however, blocks proteolytic cleavage and thus activation of SREBP-1c (Rochira et al 2013) independent of transcription.…”
Section: 5-diiodo-l-thyroninementioning
confidence: 95%
“…Lin et al (1996b) demonstrated that thyroid hormone can potentiate interferon gamma-induced antiviral states in a PKCdependent manner. In Hep G cells, T 3 causes a timedependent PKC-a cytosol-to-membrane translocation after 5 min and up to 10 min of treatment, and this activation attenuates the stimulatory effect of T 3 on SREBP1 expression (Gnoni et al 2012). Similarly, thyroid hormone application to cultured myoblasts promoted PKC translocation from the cytosol to the membrane in a PLC-dependent manner (D'Arezzo et al 2004).…”
Section: Influence Of Thyroid Hormone On the Adenylyl Cyclasecamp -Pkmentioning
confidence: 96%
“…Although the genomic effect of T 3 is the down-regulation of hepatic mouse SREBP1 expression (Hashimoto et al 2006b) and the upregulation of hepatic human SREBP1 (Kawai et al 2004), two other pathways classically associated with insulin signalling have also been associated with T 3 regulation of human SREBP1. Recently, T 3 -induced SREBP1 expression in the human hepatocarcinoma cell line (Hep G) was attenuated by Akt or ERK inhibition (Gnoni et al 2012). However, although the T 3 effect on ERK activation persisted with the use of agarose-conjugated T 3 , Akt activation by T 3 was abolished, suggesting that T 3 interacts with a membrane surface receptor, such as integrin avb3, to activate ERK (Gnoni et al 2012).…”
Section: Non-classic Pathways Of Thyroid Hormone Actions In Lipid Hommentioning
confidence: 99%
See 1 more Smart Citation